Implementación de un sistema de control interno en la clìnica de especialidades central ubicada en el cantón Salcedo, provincia de Cotopaxi en el periodo enero- marzo del 2016 - Quinga Hisbez, Jessica Paola (2016)
This research was conducted at the "Central" Clinic Specialties in order to facilitate the management of financial and administrative resources through an internal control system, using the same hierarchy in jobs is defined, objectively determines the functions and methods, technical procedures, established to achieve the objectives. In the process of "Implementation of an internal control system under the COSO I (Committee of Sponsoring Organizations) report." Methods and techniques which allowed us to identify the responsibilities and separation of functions within the organization was used. By applying interviews and surveys to administrative and medical employees could learn about the different functions performed by employees of the clinic….